EVALUASI SISTEM PENYIAPAN GURU UNTUK MENGAJAR PADA JENJANG PENDIDIKAN DASAR - Sili Sabon, Simon; Widodo (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2021)
This study aims to analyze: (i) the teacher education system, (ii) the accreditation status of teacher’s colleges and study programs, (iii) the fulfillment of lecturer standards, (iv) the quality of student input, and (v) the quality of student internships. Study approach is a mix of quantitative and qualitative. The study utilizes secondary data from Higher Education Database and National Accreditation Board for Higher Education. Also used is survey data with students in four institutions around Jakarta. The study findings show that the teacher education system has changed for the better, but has not been implemented strictly. Previously, graduates of undergraduate education could immediately become teachers, but after the issuance of Minister of Education and Culture Regulation No 87/2013, a bachelor of education must take Teacher Professional Education first if he wants to become a teacher. Another study finding is that most of the study programs have not been accredited. Some study programs that have been accredited, only get a C grade. Regarding the standard of lecturers, some teacher’s colleges have met the minimum standard of having a master’s degree for lecturers. The number of lecturers at certain teacher’s colleges is excessive so that the workload is less than the standard. The quality of student input is quite good. Most students feel that they have had sufficient experience during their internship. The study 50 recommends that the ministry and teacher’s colleges apply Minister of Education and Culture Regulation No 87/2013 to produce professional teachers. The Ministry of Education and Culture must work closely with local governments so that teacher recruitment only accepts the graduates from teacher professional education. Teacher professional education must prioritize quality by only accepting graduates with Bachelor’s degree in education. If there is a study program that does not meet the requirements, it should be proposed to have its operational permit terminated. Studi ini bertujuan menganalisis: (i) sistem pendidikan keguruan, (ii) status akreditasi lembaga pendidikan keguruan dan program studi, (iii) pemenuhan standar dosen, (iv) mutu input mahasiswa, dan (v) mutu magang mahasiswa. Pendekatan studi menggunakan campuran kuantitatif dan kualitatif. Studi memanfaatkan data sekunder dari Pangkalan Data Pendidikan Tinggi dan Badan Akreditasi Nasional Perguruan Tinggi. Digunakan pula data survei dengan mahasiswa di empat lembaga di sekitar Jakarta. Temuan studi menunjukkan bahwa sistem pendidikan keguruan mengalami perubahan ke arah yang lebih baik, namun belum diimplementasikan secara ketat. Sebelumnya lulusan sarjana pendidikan bisa langsung menjadi guru, namun setelah terbitnya Peraturan Menteri Pendidikan dan Kebudayaan Nomor 87/2013, seorang sarjana pendidikan harus mengikuti Pendidikan Profesi Guru terlebih dahulu jika ingin menjadi guru. Temuan studi lainnya yaitu sebagian besar program studi belum terakreditasi. program studi yang sudah terakreditasi, sebagian hanya memperoleh nilai C. Terkait standar dosen, sebagian lembaga pendidikan keguruan sudah memenuhi standar minimal berpendidikan pasca sarjana. Jumlah dosen pada lembaga pendidikan keguruan tertentu berlebih sehingga beban kerjanya kurang dari standar. Mutu input mahasiswa sudah cukup baik. Sebagian besar mahasiswa merasa telah mendapat pengalaman memadai dari magang. Kajian merekomendasikan agar kementerian dan lembaga pendidikan keguruan menerapkan Peraturan Menteri Pendidikan dan Kebudayaan Nomor 87/2013 untuk menghasilkan guru profesional. Kementerian Pendidikan dan Kebudayaan harus bekerja sama dengan pemerintah daerah agar rekrutmen guru hanya menerima lulusan pendidikan profesi guru. Pendidikan profesi guru harus mengutamakan mutu sehingga hanya menerima lulusan sarjana pendidikan. Jika ada program studi yang tidak memenuhi persyaratan, sebaiknya diusulkan untuk dihentikan ijin operasionalnya.